A Strategic Plan for Renewable Energy Transition in a Coal Dependent Region using Participatory Backcasting: The Case of South Kalimantan Province in Indonesia - al Irsyad, Muhammad Indra; Quist, Jaco; Rahayu , Harkunti; Blok, Kornelis (International Journal of Sustainable Energy Planning and Management, 2025)
In this study participatory backcasting was refined to combine the use of existing visions in combination with stakeholder engagement and road-mapping and applied to the regional energy transition in Indonesia’s South Kalimantan Province, where the gross regional domestic product strongly depends on coal mining. Based on document analysis, interviews, consultations, and a focus group discussion, we determined necessary changes, driving factors and challenges, and co-created a roadmap towards the preferred Nett Zero Emission vision. The roadmap proposes: (1) to increase the capacity of renewable energy, particularly wind and solar, along with battery energy storage systems; (2) to transform economic activities currently based on coal towards bioenergy hubs and to build a regional economy based on renewable energy; (3) to enhance the quality of data on renewable energy potential, power grid flexibility, and variable renewable plants, and (4) to shift culture and behaviour towards energy saving, energy communities, electrification of lifestyles, and the use of renewable energy in industry. Our study contributes to the literature on participatory backcasting by a case on the clean energy transition in fossil fuel-rich nations in the Global South and advances backcasting by using existing visions instead of generating one or several new visions.